Succinato de cloranfenicol restaura o acúmulo de células polimorfonucleares na pleurisia induzida pela carragenina em ratos diabéticos - Moraes, Julieta Rodini Engrácia de (1998)
We investigated the effect of chloramphenicol succinate (30 mg/kg, every 12 h for 4 days, ip) on the reduced polymorphonuclear leukocytes (PMN) accumulation in carrageenin-induced pleurisy (150 mug) in diabetic (alloxan, 40 mg/kg, IV) rats (Wistar, males, 180-320 g, n = 12). Chloramphenicol produced an increase (p<0.05) on PMN count in pleural exudate of 36% in normal animals. In the animals non-treated with chloramphenicol the diabetes state reduced (p<0.05) the accumulation of PMN cells by 45%. In diabetic animals treated with chloramphenicol the number of PMN in pleural exudate was similar to the one observed in the control group. Total and differential counts of leukocytes in the peripheral blood were similar between groups before and 4 h after the carrageenin-injection.